Multiwavelength detectability of isolated black holes in the Milky Way. Issue 3 (27th May 2021) - Scarcella, Francesca; Gaggero, Daniele; Connors, Riley; Manshanden, Julien; Ricotti, Massimo; Bertone, Gianfranco
ABSTRACT: Isolated black holes in our Galaxy have eluded detection so far. We present here a comprehensive study on the detectability of isolated stellar-mass astrophysical black holes that accrete interstellar gas from molecular clouds in both the local region and the Central Molecular Zone. We adopt a state-of-the-art model for the accretion physics backed up by numerical simulations, and study the number of observable sources in both the radio and X-ray band, as a function of a variety of parameters. We discuss in particular the impact of the astrophysical uncertainties on our prediction for the number of bright X-ray sources in the central region of the Galaxy. We finally consider future developments in the radio domain and assess the potential of SKA to detect a population of astrophysical black holes accreting gas in our Galaxy.